Perisai yang Lembut: Peran Perempuan Dayak Meratus dalam Mempertahankan Keberlanjutan Hutan Tropis - Nabawi, Ahmad; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2025)
The massive ecological damage has a very significant impact on all elements of life, especially communities on the edge of the forest. This study aims to describe how the internalization of feminine values and the spirit of ecofeminism contributes to the sustainability of tropical forests. This study uses a qualitative approach, with a phenomenological research type. The research location is in Batu Perahu Village, Batang Alai Timur District, Hulu Sungai Tengah Regency. Data collection was carried out through participant observation, semi-structured interviews, documentation, and literature studies. Data were analyzed using Manual Data Analysis Procedures (MDAP). The results of the study indicate that Dayak Meratus women in Batu Perahu Village play an important role in maintaining the sustainability of tropical forests. This role is implemented through subsistence farming. Women in Batu Perahu Village know various diversities. This diversity is a woman's expertise. The existing natural resources are utilized and managed by prioritizing feminine values. The dominance of feminine values ​​arises due to the realization of gender equality and social inclusion. Therefore, women do not experience gender discrimination, which has an impact on the fulfillment of women's eco-social and cultural rights, which have implications for the realization of tropical forest sustainability. This study suggests that the construction of complete gender equality must be realized and maintained. Both men and women must have equal access and opportunities in the use of natural resources. Given the important role that women have, especially in maintaining ecological sustainability.